The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1751-0759-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia as a prognostic risk factor for health problems: a brief review of epidemiological studies

Abstract: The number of articles on alexithymia has been steadily increasing since the word “alexithymia” was coined in the 1970s to denote a common characteristic that is observed among classic psychosomatic patients in whom therapy was unsuccessful. Alexithymia, a disorder of affect regulation, has been suggested to be broadly associated with various mental and physical health problems. However, most available evidence is based on anecdotal reports or cross-sectional observations. To clarify the predictive value of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 77 publications
2
60
0
6
Order By: Relevance
“…Future studies should confirm the interaction between emotional distress and the strength of internal or external stimuli on symptom perception in patients with alexithymia. The findings of such a study may partly explain unhealthy behaviors, including the delay in health care utilization, low compliance, or other behaviors that can lead to poor health outcomes, including early death, that have been consistently observed in the population with alexithymia (11).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should confirm the interaction between emotional distress and the strength of internal or external stimuli on symptom perception in patients with alexithymia. The findings of such a study may partly explain unhealthy behaviors, including the delay in health care utilization, low compliance, or other behaviors that can lead to poor health outcomes, including early death, that have been consistently observed in the population with alexithymia (11).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the subscales of the TAS-20 as described originally by Bagby et al (1994a) particularly the scale "difficulty identifying feelings" showed strong associations with a wide range of psychopathological symptoms (Grabe et al, 2004). Kojima (2012) reviews relevant studies on alexithymia as a prognostic factor for health problems. Especially in patients with somatoform disorder the difficulty to identify feelings as described by the first TAS-20 subscale is seen as a relevant etiological factor (de Gucht and Heiser, 2003;Mattila et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Alexithymia is associated with depression, anxiety and addiction notably substance and alcohol abuse and has also been implicated in the pathogenesis of physical illness notably psychosomatic disease (Hintikka et al, 2001;De Rick and Vanheule, 2007;Kojima, 2012). From a conceptual point of view, alexithymia can be considered either as a state or a trait.…”
Section: Introductionmentioning
confidence: 99%